Ten Strategies for Working With Your Home Owner Association to Convert to a Florida-Friendly Yard - Gail Hansen de Chapman; Claire Lewis (EDIS)
Many homeowners are beginning to rethink their landscapes for several reasons, including mandated water and fertilizer restrictions, increasing maintenance costs, and concern for the environment. But over sixty million people now live in neighborhoods governed by Homeowner Associations, whose regulations can make it difficult to implement some changes by mandating types of plants, percentages of turf and plant material, location of plant materials, and restricting specialty gardens to back yards. More environmentally sound landscapes are possible with careful planning and design, and by using an educated and knowledgeable approach to working with the HOA board to gain approval for a new landscape. This 9-page fact sheet offers several strategies for working within HOA regulations to gain approval for a Florida-Friendly landscape. Written by Gail Hansen and Claire Lewis, and published by the UF Department of Environmental Horticulture, February 2015. (Photo credit: Florida-Friendly Landscaping™ Program)